Effects of calcination temperature on crystal structure and photocatalytic activity of CaIn2O4/ In2O3 composites. Issue 17 (1st December 2019) - Zhang, Qinku; Cheah, Pohlee; Han, Fengxiang; Dai, Qilin; Yan, Yonghua; Pramanik, Avijit; Chandra Ray, Paresh
Abstract: CaIn2O4/In2O3 composites were prepared with electrospinning method. The samples were calcined at different temperatures and characterized with XRD, SEM, UV–Vis DRS, N2 adsorption-desorption isotherm, FT-IR and Raman spectroscopy. The effects of calcination temperature on crystal phase, morphology, band gap energy (Eg), BET specific surface area and pore size of the CaIn2O4/In2O3 composites were investigated. The degradation of methyl blue (MB) was used to evaluate the photocatalytic activity of the CaIn2O4/In2O3 composites under the irradiation of simulated sunlight. The results showed significant effect of calcination temperature on crystal phase, morphology and photocatalytic performance of the composites. When calcination temperatures were 700 °C and 1000 °C respectively, the CaIn2O4/In2O3 composites showed nanobelts and nanoparticles with high photocatalytic activity. The degradation rate of MB was 76% and 92% after simulated sunlight irradiation for 120 min for the CaIn2O4/In2O3 composites calcined 700 °C and 1000 °C, respectively. This is attributed to the large specific surface area, the efficient separation and transportation of photogenerated carriers. All the results revealed that the CaIn2O4/In2O3 composites were a promising candidate in the practical application of dye wastewater treatment.